2015
DOI: 10.2217/pgs.14.168
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Chemotherapy-Induced Nausea and Vomiting

Abstract: Chemotherapy-induced nausea and vomiting (CINV) is associated with distressing adverse effects observed in patients during cytotoxic chemotherapy. One of the potential factors explaining suboptimal response to currently used antiemetics is variability in genes encoding enzymes and proteins that play a role in the action of antiemetic drugs. Pharmacogenomics studies of CINV are sparse and focus mainly on polymorphisms associated with serotonin receptor, drug metabolism and drug transport. Currently, the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 87 publications
1
14
0
Order By: Relevance
“…The hypothesis has being that individual differences in toxicity might in part depend on differences in genes involved in cell cycle progression, cell death process, DNA repair and cell functions. Based on this 48 related SNPs were studied [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ( Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis has being that individual differences in toxicity might in part depend on differences in genes involved in cell cycle progression, cell death process, DNA repair and cell functions. Based on this 48 related SNPs were studied [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ( Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Fisher et al as well as Janicki and Sugino, the CYP2D6 inhibitor quinidine reduced the in vitro hydroxylation of ondansetron, which indicates the important role of CYP2D6 in ondansetron metabolism. 5,7,9 The in vitro study by Sanwald et al confirmed that ondansetron is both CYP2D6-and CYP2E1-dependent. 8 The enzymes belonging to the cytochrome P450 family, especially CYP2D6, have an important role in the metabolism of over 25% of drugs.…”
Section: Introductionmentioning
confidence: 97%
“…Nausea and emesis have a number of etiologies, including motion-related signals that deviate from those expected, administration of toxins, exposure to radiation, migraine, gastrointestinal disease, pregnancy (hormonal changes), and even psychological stimuli (e.g., stress and extreme emotional reactions, as well as classically conditioned smell and taste aversions) (Feyer et al, 2014; Hederos, 1992; Heer et al, 2006; Horn et al, 2014; Kenward et al, 2015; Matthews et al, 2014; Olden et al, 2005; Singh et al, 2016; Sugino et al, 2015; Wiesmann et al, 2015; Yates et al, 2014). There is some evidence that the prodromal signs and symptoms preceding vomiting can vary depending on the emetic trigger.…”
Section: Introductionmentioning
confidence: 99%